Opicapone: once‐daily adjunctive therapy for Parkinson's disease. Issue 2 (February 2017) - Chaplin, Steve
Abstract : Opicapone (Ongentys) is a new once‐daily catechol‐O‐methyl transferase (COMT) inhibitor with a long duration of action allowing once‐daily dosing, licensed for adjunctive therapy in adults with Parkinson's disease and end‐of‐dose motor fluctuations. This article discusses its indications, efficacy and adverse effects.